The Influence of Taxpayer Awareness, Tax Sanctions, and Tax Knowledge on Taxpayer Compliance, Moderation of Morals - Indriani; Namla Elfa Syariati; Nur Rahmah Sari (Academic Bright Collaboration, 2025)
Taxes are the main source of state revenue which plays an important role in financing development and the provision of public services. However, the level of compliance of taxpayers, especially Micro, Small, and Medium Enterprises (MSMEs), is still a challenge in the tax system in Indonesia. This study aims to analyze the influence of tax paying awareness, tax sanctions, and tax knowledge on the compliance of MSME taxpayers with morals as a moderation variable. This study uses a quantitative approach with a survey method. The research population is MSME taxpayers registered at KPP Pratama Bulukumba. Sampling was carried out using non-probability sampling techniques. Data were collected through a questionnaire on a Likert scale and analyzed using Moderated Regression Analysis (MRA).The results of the study show that tax paying awareness, tax sanctions, and tax knowledge have a positive effect on taxpayer compliance. In addition, morals have been proven to strengthen the influence of tax payment awareness on taxpayer compliance, but do not moderate the influence of tax sanctions and tax knowledge on compliance. These findings suggest that moral factors play a selective role in shaping tax compliance, particularly when interacting with awareness-based internal factors. Theoretically, this study expands the application of the Theory of Planned Behavior by integrating moral values (morals) as a moderation variable in the context of taxation. Practically, the results of this study imply that efforts to improve tax compliance not only need to emphasize the enforcement of sanctions and increase tax knowledge, but also the strengthening of taxpayers' awareness and moral values to encourage voluntary and sustainable compliance.